(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
The results of the study of the spontaneous plant cover of the National Dendrological Park «Sofiyivka» of the NAS of Ukraine (Uman, Cherkasy region) are presented. 115 taxa (species and subspecies) registered on the studied Dendrological Park for the first time and are absent in the previous works. There is a list of the taxa, which includes one species of horsetail and fern, as well as representatives of the representatives of Monodicots and Eudicots angiosperms. Among them native plants – 52, alien plants – 63. According to new data, 479 native plants and 164 alien plants are represented in the «Sofiyivka» spontaneous flora, and the level of adventisation of the spontaneous flora is 25.4%. It which is less than in other large introductory botanical institutions of the Right Bank Forest-Steppe as M.M. Gryshko National Botanical Garden (41.9 %) and the Dendrological Park «Alexandria» (31.2 %), that is, in the structure of vegetation of the «Sofiyivka» alien species have a relatively small impact. Among the newly discovered adventitious species, a high proportion (32 taxa from 63) have escaped plants, which confirms the steady trend towards significant adventitia of the flora due to the naturalization of ergasiophytes. Additionally, information is provided on individual ergasiophytes, which are in the initial stages of naturalization. Examples of ergasgasiolypophytes (cultural relics) are given. Such plants have the appearance of wild, but are remnants of former plantations, and therefore can not be included in the spontaneous flora. Attention is paid to the fact that the spontaneous flora of Dendrological Park «Sofiyivka» is of great importance in the taxonomic diversity of both the urban flora of Uman and the regional flora of Cherkasy region. Thus, for the first time for the flora of Cherkasy region 16 new taxa are given: Acalypha australis, Allium altissimum, Claytonia perfoliata, Juglans cinerea, Lolium × elongatum, Nepeta racemosa, Oxalis fontana subsp. villicaulis, Philadelphus pubescens, Plantago uliginosa, Polygonum arenastrum subsp. calcatum, Ranunculus acris subsp. friesianus, Solanum nigrum subsp. schultesii, Symphyotrichum lanceolatum, Symphytum asperum, Tilia platyphyllos, Vincetoxicum hirundinaria subsp. laxum. Due to the rich taxonomic composition of ergasiophytes in "Sofiyivka" Uman is a center of replenishment of flora with new foreign plants in our country. In this regard, it is important to generalize the taxonomic diversity of the urban flora of Uman and the flora of Cherkasy region.